Biophysical characterization of the energy and TonB-dependence of the ferric enterobactin transport protein FepA - Jordan, Lorne Donnell (Kansas State University, 2015)
The goal of the research included in this dissertation is to provide a more complete model of the role of TonB, an energy transducing protein that resides in the inner membrane and is an essential component of the iron transport of Escherichia coli under iron-starved conditions. Using fluorescent hybrid proteins, the anisotropy of TonB in the cytoplasmic membrane (CM) of Escherichia coli was determined. With the aim of understanding the bioenergetics of outer membrane (OM) iron transport, the dependence of TonB motion on the electrochemical gradient and the effect of CM proteins ExbB and ExbD on this phenomenon was monitored and analyzed. The native E. coli siderophore, enterobactin chelates Fe⁺³ in the environment and ferric enterobactin (FeEnt) enters the cell by energy- and TonB-dependent uptake through FepA, its OM transporter. The TonB-ExbBD complex in the CM is hypothesized to transfer energy to OM transporters such as FepA. We observed the polarization of GFPTonB hybrid proteins and used metabolic inhibitors (CCCP, azide and dinitrophenol) and chromosomal deletions of exbBD to study these questions. The results showed higher anisotropy (R) values for GFP-TonB in energy-depleted cells, and lower R-values in bacteria lacking ExbBD. Metabolic inhibitors did not change the anisotropy of GFP-TonB in ΔexbBD cells. These findings suggest that TonB undergoes constant, energized motion in the bacterial CM, and that ExbBD mediates its coupling to the electrochemical gradient. By spectroscopic analyses of extrinsic fluorophore labeled site-directed Cys residues in 7 surface loops of Escherichia coli FepA, binding and transport of ferric enterobactin (FeEnt) was characterized. Changes in fluorescence emissions reflected conformational motion of loops that altered the environment of the fluorophore, and we observed these dynamics as quenching phenomena during FeEnt binding and transport in living cells or outer membrane vesicles. Cys residues in each of the 7 surface loops (L2, L3, L4, L5, L7 L8, and L11) behaved individually and characteristically with regard to both fluorophore maleimide reactivity and conformational motion. Fluorescence measurements of FeEnt transport, by either microscopic or spectroscopic methodologies, demonstrated that ligand uptake occurs uniformly throughout the cell envelope, and susceptibility of FeEnt uptake to the proton ionophore m-chlorophenyl hydrazone (CCCP) at concentrations as low as 5 uM. The latter result recapitulates the sensitivity of inner membrane major facilitator transporters to CCCP (Kaback, 1974), providing further evidence of the electrochemical gradient as a driving force for TonB-dependent metal transport.
Keywords: Iron transport; Escherichia coli; TonB-dependent; Fluorescence anisotropy; FepA; Enterobactin; Biochemistry (0487); Biophysics (0786)